Surface Mycosis in Athletes from the School of Education, University of Carabobo - Amarily Perelli; Vita Calzolaio; Emy González (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2012)
Dermatophytosis is one of the most common health problems worldwide, with greater incidence in tropical and subtropical countries, most often in males. Athletes are constantly predisposed to suffering from fungal infections due to the variability of individual and environmental conditions. The objective was to determine the prevalence of etiological agents causing superficial mycosis in athletes from the School of Educational Sciences at the University of Carabobo. The sample was represented by 71 athletes from different disciplines that had lesions suspected of being surface mycosis on skin and nails; a direct examination was made with KOH, adhesive tape and cultivation on Lactrimel agar. The obtained isolates were examined directly with lactophenol blue and microculture to identify the etiologic agent. It was found that 63.4% of the athletes had lesions by dermatophytes, identifying the species T. rubrum (23.9%), T. mentagrophytes (19.7%) and E. floccosum (19.7%); in 36.6% of lesions, the yeast Malassezia furfur (29.6%) and Malassezia ovalis (7.1%) were identified; males were the most affected. The findings are relevant because these agents take advantage of adverse conditions to colonize and cause lesions that could decrease athletic performance.